Objective Economics : How Ayn Rand's Philosophy Changes Everything about Economics. - Buechner, M. Northrup (University Press of America, 2011)
Every price is set by someone; this is where economics begins. Building on that fundamental idea and on Ayn Rand's philosophy of Objectivism, Objective Economics transforms economics. The thesis of this book is that Ayn Rand's concept of "objective" is the indispensible base of valid economic thought. Consistently applying this idea across the board, the author reaches a general theory of price for the first time in the history of economic thought. This theory of price then provides a valid base for explaining how a free.